Analisis Kimia dari Serat Kayu Bangkal (Nauclea officinalis) sebagai Alternatif Bahan Baku Pulp Kertas (Chemical Analysis of Bangkal (Nauclea Officinalis) Wood Fibers as Raw Material Alternative of Pulp & Paper) - Herlina Herlina; Wiwin Tyas Istikowati, Ph.D.; Fatriani Fatriani (Kementerian Perindustrian, 2018)
South Kalimantan has considerable natural forests and many types of timber that have not yet been optimally utilized, such as Bangkal tree (Nauclea officinalis). The purpose of this research was to analyze chemical components, dimensional fibers characteristic, and suitability of Bangkal wood as a raw material of pulp and paper. The results obtained from this study revealed that the chemical content of Bangkal wood consisted of 3.00% extractive, 30.00% lignin, 16% hemicellulose, and 50.50% cellulose. The anatomy of Bangkal wood were 1.40 mm in fiber length 1.40 mm, 1.20 μm in fiber diameter, 5.00 μm in lumen diameter, and 3.25 μm in cell wall thickness. Derived fiber values comprised Runkel Ratio (0.43), Power Weaving (66.00), Muhsteph Ratio (99.80%), Coefficient of Rigidity (0.20), and Flexibility Ratio (0.71). Based on the chemical components and quality of Bangkal wood fiber, that wood could be used as a raw material of pulp and paper.